Patterns of Organization and Records Creation in Scientific Research: The Work of the American Institute of Physics - Fortier, Normand (Archivaria, 2002)
The author reviews the study on multi-institutional scientific collaborations conducted by the American Institute of Physics (AIP) from 1989 to 2001. He puts the study in the context of documentation strategy research and its relevance to the appraisal of the records of scientific research. The AIP reports offer archivists much valuable content regarding patterns of organization and their effects on records creation and accumulation. RÉSUMÉ L'article porte sur l'étude menée de 1989 à 2001 par l'American Institute of Physics sur les collaborations scientifiques multi-institutionnelles. L'auteur analyse cette étude dans le contexte de la recherche en stratégie de documentation et en évalue la pertinence pour l'évaluation des documents créés au cours de la recherche scientifique. Il conclut que le travail de l'AIP offre aux archivistes un éclairage précieux sur les formes d'organisation et leurs effets sur la création et l'accumulation de documents.